Hybrid Silver Nanoparticles–Purple Sweet Potato (Ipomoea batatas L.) Peels as a Prospective Adsorbent for Bromophenol Blue Removal - Saputra, Mirza Ardella; Semendawai, Bastoni; Firmansyah, Mochamad Lutfi (Journal of Advanced Technology and Multidiscipline, 2025)
Water pollution caused by dye effluents has become a global problem, for example in the textile, paper, and food industries. One common type of dye waste is bromophenol blue, which is considered to pose a low level of danger, but frequent exposure to its waste can cause skin irritation. This research was conducted using silver nanoparticles synthesized with purple sweet potato peels, which are rich in anthocyanin content so that it can be used as an active reducing agent and produce an adsorbent used for dye waste removal. Combination of biogenic-chemical method was chosen due to its simplicity, cost-effectiveness, and lower toxicity. Characterization of the obtained nanomaterials included UV-Vis spectroscopy, FTIR, SEM-EDX, and XRD. The results showed that the average crystal size of pure IBpe and the three IBpe-AgNPs were 7.09 nm, 8.68 nm, and 13.99 nm with an FCC crystal shape. The average particle sizes of the three IBpe-AgNPs were 82.76 nm, 85.72 nm, and 99.78 nm, with an almost spherical shape. The research found that IBpe-AgNP 1:9 demonstrated the highest adsorption efficiency of 77.24% compared to the other samples. In terms of desorption efficiency, the IBpe-AgNP 1:3 sample showed the highest value at 27.54% compared to the other three samples. Furthermore, the reuse test revealed that the IBpe-AgNP 1:9 sample had the highest reuse value at 27.02% compared to the other samples, showing the same trend as the first adsorption.